Characterizing Health-Related Quality of Life by Ambulatory Status in Patients with Spinal Metastases. Issue 2 (15th January 2022) - Schoenfeld, Andrew J.; Yeung, Caleb M.; Tobert, Daniel G.; Nguyen, Lananh; Passias, Peter G.; Shin, John H.; Kang, James D.; Ferrone, Marco L.
Abstract : Study Design: Retrospective review of prospective longitudinal data. Objective: To determine health-related quality of life (HRQL) utilities associated with specific ambulatory states in patients with spinal metastases: independent, ambulatory with assistance, and nonambulatory. Summary of Background Data: It is assumed that HRQL is aligned with ambulatory ability in patients with spinal metastases. Few studies have effectively considered these parameters while also accounting for clinical confounders. Methods: We used prospective longitudinal data from patients treated at one of three tertiary medical centers (2017–2019). HRQL was characterized using the Euroquol-5-dimension (EQ5D) inventory. We performed standardized estimations of HRQL stratified by ambulatory state using generalized linear modeling that accounted for patient age at presentation, biologic sex, follow-up duration, operative or nonoperative management, and repeated measures within the same participant. Results: We evaluated 675 completed EQ5D assessments, with 430 for independent ambulators, 205 for ambulators with assistance, and 40 for nonambulators. The average age of the cohort was 61.5. The most common primary cancer was lung (20%), followed by breast (18%). Forty-one percent of assessments were performed for participants treated surgically. Mortality occurred in 51% of the cohort. The standardized EQ5D utility for patients with spinal metastases and independent ambulatory function was 0.76 (95% confidence interval [CI] 0.74, 0.78). Among those ambulatory with assistance, the standardized EQ5D utility was 0.59 (95% CI 0.57, 0.61). For nonambulators, the standardized EQ5D utility was 0.14 (95% CI 0.09, 0.19). Conclusion: Patients with spinal metastases and independent ambulatory function have an HRQL similar to patients with primary cancers and no spinal involvement. Loss of ambulatory ability leads to a 22% decrease in HRQL for ambulation with assistance and an 82% reduction among nonambulators. Given prior studies demonstrate superior maintenance of ambulatory function with surgery for spinal metastases, our results support surgical consideration to the extent that it is clinically warranted. Level of Evidence: 3 Abstract : We characterized health-related quality of life (HRQL) utilities associated with specific ambulatory states encountered in patients with spinal metastases. Patients with spinal metastases who can maintain independent ambulatory function have a HRQL similar to patients with primary cancers and no spinal involvement.